Investigating the causal effects of smoking, sleep, and BMI on major depressive disorder and bipolar disorder: a univariable and multivariable two-sample Mendelian randomization study - He, Menglin; Zhou, Jian; Li, Xuehan; Wang, Rurong (Frontiers in Psychiatry, 2023)
Background: Mental disorders, characterized as products of biopsychosocial interactions, have emerged as a leading contributor to the worldwide rise in overall morbidity and disability rates. Life's essentials can affect nearly every aspect of our lives, from physical to mental health. In this study, we try to identify the associations between life's essentials and mental disorders.Method: Three assumptions of Mendelian randomization (MR) were applied to obtain the genetic instruments associated with smoking, sleep, and body mass index (BMI) in genome-wide association studies (GWAS). Then, we conducted univariable (UVMR) and multivariable two-sample Mendelian randomization (MVMR) analyses to estimate the causal effects of these life's essentials on two major depressive disorder (MDD) and bipolar disorder (BD). Additionally, multiple sensitivity analyses were performed to evaluate the reliability and stability of the study results.